Entrepreneurship in Interpreting: A Blue Ocean Strategy Didactic Toolkit for Higher Education Interpreter Training - Aguirre Fernández Bravo, Elena; Guindal Pintado, María Dolores (HERMES - Journal of Language and Communication in Business, 2020)
This article aims at presenting the reader with a didactic proposal for training higher education interpreting students in entrepreneurial skills by means of introducing a toolkit based on the Blue Ocean Strategy marketing theory. First, the reasons why entrepreneurship is necessary and should thus be an integral part of the interpreting curriculum will be put forward. Second, the Blue Ocean Strategy and its special suitability for the interpreting market will be argued. Third, the transposition of this theory into the interpreting classroom will be explained, with a focus on the approach and development of the lesson plan and didactic materials, which were devised on the basis of a flipped learning teaching methodology. Fourth, the results of the pilot implementation of this toolkit in the dialogue interpreting course Interpretación II: Técnicas de mediación intercultural, a 6 ECTS B.A. in Translation and Interpreting course at the Universidad Pontificia Comillas (Madrid), will be discussed by way of analysing 45 responses to questionnaires designed with the purpose of shedding light on whether perceptions of the interpreting market substantially differ among students who made part of the experimental group that took the Blue Ocean Strategy pilot class (18 subjects) and the control group (27 subjects), who did not receive training in this marketing strategy.